Industrial experience on journalism education curriculum in Malaysia - Yusof, Norhafezah; Ismail, Awan; Ismail, Rizalawati; Aripin, Norizah; Kassim, Azhar; Ishak, Mohd. Sobhi (UUM Press, 2017)
The aim of the study is to examine industrial perspective on journalism education curriculum in Malaysia. Curriculum plays an important role in providing quality education for students. This study focuses on the curriculum aspect of journalism education. Journalism is a dynamic field that integrates industrial experience and fundamental knowledge gained from higher educational institutions. It has been debated by scholars in the field that it is important for the academia to consider industrial players in shaping the curriculum of the field. Thus, in line with the argument, this study is conducted to investigate the industrial perspective on journalism education in Malaysia. Drawing from the researchers’ experiences and guidelines from the Malaysian Qualifications Agency, the researchers adapted the Taba Model as the theoretical framework. The study used semi-structured interview method. Fifteen experts were interviewed. They have served more than 10 years in media industry and hold various executive positions. The interview protocol was developed based on literature review and guidelines of Communication and Media Studies curriculum review. The interviews were conducted at the interviewees’ offices or homes. Each interview ranged from 1 to 2 hours. The data was analysed using thematic analysis. The findings revealed four main themes: 1) Strong general knowledge requirement, 2) Right skills mattered, 3) Interest in the field – ability to adapt and learn, and 4) Specialised knowledge. This supported the view that industry and academia have to collaborate extensively in producing high quality graduates in journalism.